Controle de gerador de indução duplamente alimentado para auxílio na regulação de tensão em rede rural - Prigol, Jean Patrick (2017)
This work presents the power control in a double fed induction generator (DFIG) used in a wind turbine, aiming the control of active and reactive power to minimize the voltage variations in rural networks. With the insertion of these renewable energy sources in the low voltage distribution system, it is fundamental to analyze the impacts on the quality of energy at the point of connection (PC) and to implement adequate control to attend the technical requirements of the distribution procedures established by standard. An equation is presented to relate the voltage variation to the injected power in a low voltage distribution network. A typical rural network is emulated in this work to analyze this impact on the voltage variation in remote areas. The system uses traditional PI control meshes for rotor currents and active and reactive power mesh, and the references are then set to help prevent a violation of the allowable voltage variation band as per standard. Due to the fact that the insertion of active power in rural networks is the main factor of variation of the voltage in the PC, experimental results are presented to validate the developed theory and to prove the efficiency of the designed system.